Maqasid Syariah dalam Memperankan Penafsiran Kontemporer - Masruchin Masruchin (Journal Khafi : Journal Of Islamic Studies, 2024)
Abstract / Abstrak Maqasid al-Shariah assists interpreters in understanding the meanings of the verses of the Qur'an in a deeper and more relevant context to contemporary life. By utilizing maqasid al-Shariah, interpretations can provide a more comprehensive and applicable guidance. This research aims to explore the capacity of maqasid al-Shariah in understanding the verses of the Qur'an, including the work of Ibn Ashur, who has begun to apply it in interpreting the Qur'an. The methodology of this research is analytical with a literature approach. The findings of this study indicate that maqasid al-Shariah is not only a legal foundation but also enables interpreters to develop interpretations by considering the objectives of Islamic law that are more contemporary and relevant to the dynamics of the times. Maqasid syariah membantu para mufassir dalam memahami makna ayat-ayat Al-Qur'an yang lebih mendalam dan relevan dengan konteks kehidupan saat ini. Dengan menggunakan maqasid syariah, tafsir dapat memberikan panduan yang lebih komprehensif dan aplikatif. Penelitian ini bertujuan untuk mengeksplor kapasitas maqasid syariah dalam memahami ayat-ayat al-Qur’an, diantaranya Ibn Asyur yang telah memulai menerapkannya dalam memahami ayat al-Qur’an. Metodologi penelitian ini adalah berbentuk analisis dengan pendekatan pustaka. Hasil temuan dalam penelitian ini menunjukkan bahwa maqasid Syariah bukan hanya sebagai landasan hokum, akan tetapi memungkinkan para mufassir untuk mengembangkan penafsiran dengan mempertimbangkan tujuan-tujuan hukum Islam yang lebih kontemporer dan relevan dengan dinamika zaman.